M-KIA 79 application version 2.0 for Integrated Healthcare Center services at Posyandu Kenangan in Samarinda - Fetty Poerwita Sary; Mochamad Yudha Febrianta; Sri Widiyanesti; Milleniartha Moslem (University of Merdeka Malang, 2022)
Posyandu is a form of Community Based Health Efforts which is managed from, by, for, and with the community, in order to empower the community and provide convenience to the community in obtaining basic health services. Based on field data, it was found that the problems faced by the Posyandu Kenangan were the limited number of cadres, unrepresentative places due to frequent flooding, lack of awareness about Posyandu and data histories that was often lost and scattered due to flooding. The purpose of this activity is to develop an application called M-KIA 79 Version 2.0. The implementation of this community service will fulfill the SDG's goals, namely good health and welfare, quality education and sustainable cities and communities. This community service is carried out in the form of producing the M-KIA 79 Application which will be used by Posyandu Kenangan’s cadres in recording the health history of infants, toddlers, and pregnant women and socializing the use of the M-KIA 79 Application. The implementation of making this application is carried out using several approaches to Design Analysis and System Design. The results of this study are in terms of socialization of the M-KIA 79 application, the community response is 95% agree and this application can be well received by the community, posyandu cadres and health centers.